Effect of rainfall characteristics on the sewer sediment, hydrograph, and pollutant discharge of combined sewer overflow. (1st February 2022) - Yu, Dawei; Dian, Liu; Hai, Yonglong; Randall, Mark T.; Liu, Li; Liu, Jibao; Zhang, Junya; Zheng, Xiang; Wei, Yuansong
Abstract: Significant management needs raised in urban sewer system to facilitate urban resilience to rainstorm. The work investigated the effects of temporal evolution of rainfall on hydrograph and pollutant discharge of CSO over an intensive observation period of 12 months, with special attention to differences in temporal scale for supporting management decision making. The characteristics of rainfall in different temporal scales helped overflow-risk identification and assessment. Prolonged dry seasons over 112 days in the CSO monitored year 2018 increased the sediment buildup in the pipes. The built sediment was mostly flushed out to overflow (and the treatment facility) by initial rainfall during 47 h. Following CSO hydraulics and pollutant discharge follows initial peak patterns which responded to rainfall patterns. Results of Redundancy analysis and network analysis showed that the combined effects of rainfall, urbanization, and sediments as "CSO troika" are the driving forces for CSO pollutants in the long-term. The improved characterization of CSO events and the associated pollutants has refined our understanding of how overflow hydrograph and pollutant discharge responds to rainfall temporally, which methodology supported decision making in the combining source/process control with terminal management for facilizing urban resilience. Graphical abstract: Image 1 Highlights: The sophisticated investigation of CSOs supported decision making by methodology. Rainfall pattern and sewer sediment together shaped overflow pollutants. Combined sewer sediments were built-up in dry season and flushed out in wet season. Overflow pollutants SS, COD, and TN follows peak-sustain pattern similar with rain. Temporal evolution of CSOs' hydrograph and pollutants discharge were investigated.